PERBANDINGAN KUALITAS HIDUP PASIEN DISPEPSIA YANG MENGGUNAKANLANSOPRAZOLDENGAN INJEKSI RANITIDIN DI RSUD PANEMBAHAN SENOPATI BANTUL YOGYAKARTA - , Okky Puspitasari S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Dyspepsia is a complaint relating to eat and include the patient's quality of life. The purpose of this study was to determine differences in the quality of life of patients with dyspepsia at RSUD Panembahan Senopati Bantul Yogyakarta who received lansoprazole (2x30mg) or ranitidine injection (2x25mg / ml) by using a quality of life questionnaire Nepean Dyspepsia Index Indonesia (NDII). The method is a cross-sectional study with consecutive sampling done during the period April to June 2014, data were collected from the results of quality of life questionnaires NDII currently hospitalized patients. Analysis of the data with the scoring system, the chi-square and independent t-test. The subjects of the study 30 patients (each group of 15 respondents). The results of the study there was no difference in the quality of life among patients taking lansoprazole with ranitidine injection in four domains (p> 0.05) (p = 0.315 tension), (activities of daily p = 0.290), (eating / drinking p = 0.629) , (knowledge / control p = 0.698).